Implementation of the CIPP Model in Evaluation of Religious Counseling in Kupang Women's Prison: A Conceptual Framework - Yosep Sudarso; Hendrik A.E. Lao (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article conceptually examines the application of the CIPP model to the evaluation of religious counseling at the Kupang Women's Prison. Although it is the responsibility of religious counselors, in practice, evaluations are still administrative and unstructured, making it difficult to objectively measure and assess the results. This study employed a qualitative approach with content analysis. As a result, the CIPP conceptual framework offers a more comprehensive and systematic approach that addresses the needs of inmates. Through context evaluation, it can be determined whether the religious counseling program responds to the spiritual and moral needs of inmates. Through input evaluation, the quality of the counselors, counseling materials, methods and approaches, and media used can be measured and assessed. Through process evaluation, it can be determined whether religious counseling takes place through in-depth and personal interactions. Through outcome evaluation, it can be determined whether religious counseling leads to changes in inmates' religious attitudes and behaviors. Therefore, this study recommends the implementation of the CIPP model in the evaluation of religious counseling activities.